Ca2+ handling at the mitochondria-ER contact sites in neurodegeneration. (September 2021) - Lim, Dmitry; Dematteis, Giulia; Tapella, Laura; Genazzani, Armando A.; Calì, Tito; Brini, Marisa; Verkhratsky, Alexei
Highlights: Ca 2+ is transferred from the ER directly to mitochondria at the mitochondria-ER contact sites (MERCS). Ca 2+ transferring machinery includes InsP3R-Grp75-VDAC1 complex with accessory proteins, and MCU. Efficient Ca 2+ transfer requires an ER-mitochondria distance of about 15-20 nm. Structure and composition of MERCS, as well as Ca 2+ transfer, are altered in neurodegenerative diseases. Relationships between the causes of neurodegenerative diseases and MERCS morphology, composition and Ca 2+ transfer require further investigations. Abstract: Mitochondria-endoplasmic reticulum (ER) contact sites (MERCS) are morpho-functional units, formed at the loci of close apposition of the ER-forming endomembrane and outer mitochondrial membrane (OMM). These sites contribute to fundamental cellular processes including lipid biosynthesis, autophagy, apoptosis, ER-stress and calcium (Ca 2+ ) signalling. At MERCS, Ca 2+ ions are transferred from the ER directly to mitochondria through a core protein complex composed of inositol-1, 4, 5 trisphosphate receptor (InsP3 R), voltage-gated anion channel 1 (VDAC1), mitochondrial calcium uniporter (MCU) and adaptor protein glucose-regulated protein 75 (Grp75); this complex is regulated by several associated proteins. Deregulation of ER-mitochondria Ca 2+ transfer contributes to pathogenesis of neurodegenerative and other diseases. The efficacy of Ca 2+ transfer between ER and mitochondria depends on the protein composition of MERCS, which controls ER-mitochondria interaction regulating, for example, the transversal distance between ER membrane and OMM and the extension of the longitudinal interface between ER and mitochondria. These parameters are altered in neurodegeneration. Here we overview the ER and mitochondrial Ca 2+ homeostasis, the composition of ER-mitochondrial Ca 2+ transfer machinery and alterations of the ER-mitochondria Ca 2+ transfer in three major neurodegenerative diseases: motor neurone diseases, Parkinson disease and Alzheimer's disease. Graphical abstract: Image, graphical abstract